The use of AHP method for selection of supplier - Hruška, Roman; Průša, Petr; Babić, Darko (Transport, 2014)
To increase flexibility in today’s global marketplace is needed to remain competitive and respond to rapidly changing markets. From that point of view, supplier selection represents one of the most important functions to be performed by the purchasing department. The supplier selection is a multi-criterion problem which includes both quantitative and qualitative criteria. In order to select the best suppliers, it is necessary to make a trade off between these criteria. The article deals with supplier selection using the Analytic Hierarchy Process (AHP). AHP provides a framework for making effective decisions in complex decision situations (e.g. vendor selection), helps to simplify and accelerate the natural process of decision making. AHP is a method of decomposition of complex unstructured situation into simpler components, thus creating a hierarchical system problem. The paper describes the general design of model supplier selection using the AHP with an application of the proposed model in a manufacturing company that selects a suitable supplier of three potential suppliers. The aim of this paper is to understand the strategic operating decision area of the supplier selection process and to aid decision makers with varying degrees of importance to reach consensus in rating alternative suppliers.